First‐in‐human report of MitraClip G4 implantation for severe degenerative mitral regurgitation. Issue 3 (17th February 2020) - Raghunathan, Deepa; Garcia‐Sayan, Enrique; Dhoble, Abhijeet; Smalling, Richard
Abstract: The new MitraClip G4 device (Abbott Vascular) has been recently approved by Food and Drug Administration and is currently in limited release. A patient with a large mitral regurgitation (MR) jet but a relatively small mitral valve area (MVA) was not a surgical repair candidate nor an optimal MitraClip third‐generation device candidate. Therefore, we implanted the new G4 NTW device that resulted in significant MR reduction with a 57% reduction in MVA. To our knowledge, this is the first reported clinical use of the MitraClip G4 NTW device. We find that it may provide better results than a single NTR device and less reduction in MVA than two older generation devices. Further experience is needed to optimize patient selection for the four new G4 devices available.